Effectiveness of Foot Reflexology Massage Therapy in Reducing Blood Pressure and Improving Comfort in Elderly Patients with Hypertension: A Case Study at Griya Lansia Garut Social Service Unit - Selvia; Puspita, Tantri (Nursing Case Insight Journal, 2025)
Hypertension is a major health problem among the elderly, often requiring integrated management approaches. Foot reflexology massage therapy is a non-pharmacological intervention that may reduce blood pressure and improve comfort in hypertensive elderly patients. To analyze the effectiveness of foot reflexology massage therapy in reducing blood pressure and improving comfort in an elderly patient with hypertension at the Griya Lansia Garut Social Service Unit. A descriptive case study method was used with one elderly respondent. Nursing care was implemented over three days, with foot reflexology massage as the main intervention. Pre- and post-therapy blood pressure measurements and comfort assessments were conducted. Four nursing diagnoses were identified: discomfort, sleep pattern disturbance, knowledge deficit, and risk of falls. After three days of intervention, systolic blood pressure decreased from 170/100 mmHg to 130/90 mmHg, and diastolic pressure improved. The patient reported reduced discomfort, improved sleep, and increased understanding of hypertension management. Foot reflexology massage therapy is an effective non-pharmacological intervention to reduce blood pressure and enhance comfort in elderly hypertensive patients. It should be considered as part of holistic geriatric nursing care.